Inovasi Sistem Pendidikan Islam Pada Era Revolusi Industri 4.0 di Indonesia - Rahmawati, Lusi; Maisyanah, Maisyanah; Subakti, Mohamad Faisal; Nisak, Zumrotun (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2020)
The emergence of Era 4.0 in Indonesia has an impact on the field of Islamic education, So an innovation in the Islamic education system is needed. In his writing, this study aims to provide an overview, concepts, and theories of how the Islamic education system should be in this era, especially in responding to the lifestyles of children today who are increasingly familiar with technology, some even think that technology is the most loyal friend. The results of this study state that the Islamic Education System Innovation must be implemented immediately, so that Islamic education in the midst of the times does not lose its existence, integrating technology into the Islamic education system is also a must in order to attract children to learn Islam through their gadgets. In preparing this article, the author uses a literature study approach with a qualitative method.